A composite electrode sheet, a method of manufacturing the same, and a battery
Patent Information
- Application Number
- CN202611389962.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为解决因层间物理接触不充分导致的界面结合力弱、电子/离子传输效率低等核心问题,本发明通过引入一种单层涂布与单层激光刻蚀相结合的序列化方法,在层间构建具有特定形貌的过渡结构,实现机械互锁与离子传输通道的原位集成,从而显著提升电极的机械稳定性、电化学性能及结构设计的灵活性
(1)本发明通过在集流体表面的首次刻蚀在界面处创造微观互锁结构,使第一活性层与第二活性层实现三维立体结合,而非传统的二维平面粘附,有效抑制活性材料在充放电体积变化时产生的剪切应力,从根本上解决涂层剥离问题,大幅提升电极循环寿命。
Smart Images

Figure CN122930831A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode technology, and in particular to a composite electrode sheet, its preparation method, and a battery. Background Technology
[0002] Lithium-ion batteries are currently the mainstream electrochemical energy storage devices, and their energy density, power density, and cycle life are key technical indicators. Battery electrodes, as the core components of the battery, have their structure and manufacturing processes directly affecting the overall performance of the battery.
[0003] Currently, traditional lithium-ion battery electrodes generally employ a single-layer active material coating structure, which suffers from several core defects, including long and uneven electron / ion transport paths, mechanical stress concentration leading to structural damage, difficulty in balancing high energy density with high power / long lifespan, limited current collector function, and challenges in thermal management. These defects severely restrict the improvement of overall battery performance. While existing multilayer coating technologies attempt to optimize performance through layered design, they suffer from weak interlayer bonding and low interfacial ion / electron transport efficiency.
[0004] Therefore, there is an urgent need to develop an innovative electrode structure design and manufacturing process to synergistically improve the energy density, power density, cycle stability and safety of lithium-ion batteries. Summary of the Invention
[0005] To address the core issues of weak interfacial bonding and low electron / ion transport efficiency caused by insufficient interlayer physical contact, this invention introduces a sequential method combining single-layer coating and single-layer laser etching to construct a transition structure with a specific morphology between layers. This achieves in-situ integration of mechanical interlocking and ion transport channels, thereby significantly improving the mechanical stability, electrochemical performance, and structural design flexibility of the electrode.
[0006] The first aspect of the present invention provides a composite electrode sheet, the composite electrode sheet comprising a current collector and a first active layer and a second active layer sequentially stacked on the current collector; The first active layer has a first surface away from the current collector, and a first recess is formed on the first active layer extending from the first surface toward the current collector. The second active layer covers the first surface and fills the first recess; The second active layer has a second surface away from the first active layer, and a second recess is formed from the second surface toward the current collector, and the second recess includes a shallow recess and a deep recess. The depth of the deep recess is greater than the depth of the shallow recess, and the depth of the deep recess is greater than the thickness of the second active layer.
[0007] Currently, there are many technical problems with the traditional lithium-ion battery electrode structure: (1) In the traditional thick electrode design, electrons need to pass through the active material layer laterally from the current collector to reach the reaction front, and ions also need to diffuse over a long distance in the electrolyte, resulting in uneven distribution of electron and ion conductivity inside the electrode, large electrochemical polarization in the area far from the current collector, low utilization of active material, and severe performance degradation during high-rate charging and discharging. (2) The active material undergoes large volume changes during charging and discharging, and its expansion and contraction stress cannot be effectively released and buffered within a single continuous active material layer. Stress concentration easily leads to the rupture of active particles, breakage of conductive network, and cracking of coating, accelerating performance degradation. (3) In order to improve the energy density of the battery, the surface load of the active material needs to be increased, but the thick electrode in the traditional structure will exacerbate the transmission limitation and stress problem, resulting in a decrease in rate performance and cycle life, forming a contradiction between "high energy density" and "high power density / long life". (4) Traditional copper / aluminum foil mainly serves as a current collector. The surface is mostly smooth or simply roughened. Although etching increases the bonding force, it does not change the one-dimensional electron transport path and cannot actively guide ion transport or adapt to volume changes, thus contributing little to the optimization of electrode structure. (5) The uneven reaction inside the thick electrode leads to local heat accumulation. The heat of the traditional layered structure is not easily dissipated quickly through the current collector, which may cause local overheating and affect battery safety and lifespan. This invention designs a composite electrode sheet with a specific structure. A first active layer and a second active layer are sequentially stacked on a current collector. A first recess is etched into the surface of the first active layer, and the second active layer fills the first recess and covers the first active layer. Simultaneously, a second recess with varying depths is formed. Through secondary etching, a highly efficient surface electron collection network is constructed. Furthermore, the deep and shallow channels of the first and second recesses cooperate to achieve a three-dimensional integration, fundamentally solving the coating peeling problem and significantly improving electrode cycle life. It also constitutes a "vertical ion transport channel" system, significantly shortening the diffusion distance of lithium ions in thick electrodes and improving rate performance.
[0008] Optionally, the composite electrode sheet satisfies at least one of the following characteristics: (1) The depth of the first recess is h1 = H1 × (20%~40%), where H1 is the thickness of the first active layer; (2) The width l1 of the first recess is H1×(80%~120%), where H1 is the thickness of the first active layer; (3) The depth h1 of the first recess is 3.6 μm to 10 μm; (4) The width l1 of the first recess is 14.4 μm to 30 μm; (5) The thickness H1 of the first active layer is 17 μm to 26 μm; (6) The compaction density c1 of the first active layer is 1.2 g / cm³. 3~2.4g / cm 3 .
[0009] Further optionally, the depth h1 of the first recess is H1 × (20%~40%), which can be listed as H1 × 20%, H1 × 30%, H1 × 40%, or any value within the range of H1 × (20%~40%). The preferred depth h1 of the first recess in this invention is H1 × (20%~40%). If the depth of the first recess is too shallow, the mechanical interlocking effect between the first active layer and the second active layer is weak, resulting in insufficient peeling force and interface delamination, leading to a decrease in cycle retention rate. If the depth of the first recess is too deep, the underlying structure is damaged, resulting in a decrease in capacity.
[0010] Optionally, the depth h1 of the first recess is 3.6μm to 10μm, and can be listed as 3.6μm, 5μm, 5.4μm, 6.3μm, 7.2μm, 7.5μm, or any value within the range of 3.6μm to 10μm.
[0011] In this invention, the depth h1 is the length of the first recess extending from the first surface toward the direction close to the current collector.
[0012] Optionally, the width l1 of the first recess is H1×(80%~120%), which can be listed as H1×80%, H1×100%, H1×120%, or any value within the range of H1×(80%~120%).
[0013] Optionally, the width l1 of the first recess is 14.4μm to 30μm, and can be listed as 14.4μm, 16.2μm, 18μm, 19.8μm, 20μm, 21.6μm, 25μm, 30μm, or any value within the range of 14.4μm to 30μm.
[0014] In this invention, the width l1 is the dimension of the first recess in the direction parallel to the current collector.
[0015] Optionally, the thickness H1 of the first active layer is 17μm to 26μm, and can be listed as 17μm, 18μm, 19μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, or any value within the range of 17μm to 26μm.
[0016] Optionally, the compaction density c1 of the first active layer is 1.2 g / cm³. 3 ~2.4g / cm 3 Examples include 1.2 g / cm³. 3 1.5g / cm 3 2g / cm 3 2.4g / cm 3It can also be 1.2 g / cm³. 3 ~2.4g / cm 3 Any value within the range.
[0017] Optionally, the composite electrode sheet satisfies at least one of the following characteristics: (1) The depth h of the shallow concave portion 2.1 =H1×(50%~70%), where H1 is the thickness of the first active layer; (2) The depth h of the deep recess 2.2 =c2×[c2 / (c1+c2)]×A×H, where c1 and c2 are the compaction densities of the first and second active layers, respectively, H is the total thickness of the composite electrode sheet, and A is the system constant; (3) The width l2 of the shallow recess and the width l3 of the deep recess are consistent, and each is independently l1×(80%~120%); (4) The depth h of the shallow concave portion 2.1 Its thickness ranges from 9μm to 17.5μm; (5) The depth h of the deep recess 2.2 The thickness ranges from 35μm to 55μm. (6) The width l2 of the shallow recess and the width l3 of the deep recess are each independently 14.4 μm to 30 μm; (7) The compaction density c2 of the second active layer is 1.6 g / cm³. 3 ~3.2g / cm 3 ; (8) The ratio of the area of the deep recess to the total area of the composite electrode sheet is c2 / (c1+c2)×ε, where c1 and c2 are the compaction densities of the first active layer and the second active layer, respectively, and ε is the total porosity of the composite electrode sheet. (9) The area of the deep recess accounts for 14% to 18% of the total area of the composite electrode sheet.
[0018] Further optionally, the depth h of the shallow recess 2.1 =H1×(50%~70%), which can be listed as H1×50%, H1×60%, H1×70%, or any value within the range of H1×(50%~70%). The depth h of the shallow concave portion in this invention... 2.1 The preferred value is H1×(50%~70%), when h 2.1 Below 50% H1, ion channels become discontinuous, leading to a severe decrease in rate performance; when h 2.1 When the H1 content exceeds 70%, the structural integrity of the first active layer begins to be compromised, and the conductive network is damaged.
[0019] Optionally, the depth h2.1 of the shallow recess is 9μm to 17.5μm; it can be listed as 9μm, 10.8μm, 12.5μm, 12.6μm, 15μm, 17.5μm, or any value within the range of 9μm to 17.5μm.
[0020] In this invention, the depth h2.1 of the shallow recess is the depth extending from the second surface toward the current collector.
[0021] Optionally, the depth h of the recessed portion 2.2 =c2×[c2 / (c1+c2)]×A×H, where c1 and c2 are the compaction densities of the first and second active layers, respectively, H is the total thickness of the composite electrode sheet, and A is a system constant, where A is 0.6 cm in the composite positive electrode sheet. 3 / g~0.65cm 3 / g; A in the composite negative electrode is 0.9cm 3 / g~1.0cm 3 / g.
[0022] Optionally, the depth h of the recessed portion 2.2 The value is 32μm to 48μm, and can be listed as 32μm, 35μm, 36μm, 38μm, 42μm, 48μm, or any value within the range of 32μm to 48μm. The deep recesses of this invention aim to form a continuous ion "highway" from the surface directly to the first active layer. When h 2.2 When the depth is too shallow, the deep recess does not reach the first active layer, limiting the rate performance; when h2,2 is too deep and the ratio is out of control, it penetrates to the aluminum foil current collector, causing a micro short circuit risk, reducing the cycle retention rate, and posing a safety hazard.
[0023] In this invention, the depth h2.2 of the recessed portion is the depth extending from the second surface toward the current collector.
[0024] Optionally, the area of the recessed portion accounts for 12% to 20% of the total area of the composite electrode sheet, which can be listed as 12%, 16%, 20%, or any value within the range of 12% to 20%. In this invention, the proportion of the recessed portion is strictly controlled. If the proportion is too low, the ion channel density is insufficient, limiting the rate capability; if the proportion is too high, the mechanical interlocking area is excessively weakened, resulting in decreased peeling force and significantly reduced cycle stability.
[0025] In this invention, the area ratio of the deep recess refers to the percentage of the projected area of the deep recess on the collector plane to the total area of the entire collector.
[0026] Optionally, the width l2 of the shallow recess and the width l3 of the deep recess are consistent, each being independently l1×(80%~120%), which can be listed as l1×80%, l1×90%, l1×100%, l1×120%, or any value within the range of l1×(80%~120%).
[0027] Optionally, the width l2 of the shallow recess and the width l3 of the deep recess are each independently 14.4μm to 30μm, and can be listed as 14.4μm, 16μm, 18μm, 20μm, 25μm, or any value within the range of 14.4μm to 30μm.
[0028] In this invention, the width l2 is the dimension of the shallow recess in the direction parallel to the current collector. The width l3 is the dimension of the deep recess in the direction parallel to the current collector.
[0029] Optionally, the composite electrode sheet satisfies at least one of the following characteristics: (1) The distribution pattern of the first recess on the first surface is grid-like, dot-matrix-like, or wavy; (2) The distribution pattern of the second recess on the second surface is grid-like, herringbone, straight, or diagonal; (3) The total thickness H of the composite electrode sheet is 54μm~66μm; (4) The total porosity ε of the composite electrode sheet is 28%~30%.
[0030] Further optionally, the total thickness H of the composite electrode sheet is 54μm~66μm, and can be listed as 55μm, 60μm, 65μm, or any value within the range of 54μm~66μm.
[0031] Optionally, the total porosity ε of the composite electrode sheet is 28%~30%, which can be listed as 28%, 29%, 30%, or any value within the range of 28%~30%.
[0032] Optionally, n active layers are stacked sequentially on the current collector, and the n active layers have an nth recess.
[0033] The first active layer to the (n-1)th active layer all satisfy: h n-1 =H n-1 ×(20%~40%), L n-1 =H n-1 ×(80%~120%), where H n-1 h represents the thickness of the (n-1)th layer of slurry after drying and curing. n-1 Represents the depth of the n-1th recess, L n-1 This represents the width of the (n-1)th concave portion.
[0034] Optionally, the nth active layer has an nth surface away from the (n-1)th active layer, and an nth recess is formed from the nth surface toward the current collector, and the nth recess includes a shallow recess and a deep recess.
[0035] Optionally, the depth h of the shallow recess n,1 =H1×(50%~70%), where the depth h of the deep recess is... n,2 =c n ×[c n / (c n +c n-1 )]×A×H, where A is a system constant, and must conform to the relationship A=0.6~0.65 (positive electrode) 0.9~1.0 (negative electrode). The area ratio of the deep recesses in the nth active layer conforms to the relationship c n / (c n +c n-1 )×ε, where c n c is the compaction density of the nth active layer. n-1 For the first n-1 Compacted density of the active layer.
[0036] The linewidth of the etching line in the nth active layer remains consistent, conforming to the relationship: L n =(80%~120%)×L n-1 .
[0037] Optionally, the composite electrode sheet is a composite negative electrode sheet, the first active layer includes a first conductive agent and a first binder, and the second active layer includes a silicon-carbon composite material, a second binder, and a second conductive agent; Both the first adhesive and the second adhesive are selected from at least one of polyvinylidene fluoride and polyacrylic acid; Both the first conductive agent and the second conductive agent are selected from at least one of conductive carbon black, vapor-grown carbon fiber, artificial graphite, or graphene. The silicon-carbon composite material comprises silicon-based materials and artificial graphite, and satisfies at least one of the following characteristics: (1) The first conductive agent includes artificial graphite, conductive carbon black and graphene; (2) The mass ratio of the artificial graphite, conductive carbon black and graphene is (82~88):(8~12):(0.5~2); (3) The first adhesive accounts for 3.5% to 4.5% of the total mass of the first active layer; (4) The mass ratio of the silicon-based material to artificial graphite is (8~18):(82~92); (5) The second conductive agent accounts for 3% to 4% of the total mass of the second active layer; (6) The second conductive agent includes conductive carbon black and vapor-grown carbon fiber, wherein the mass ratio of conductive carbon black to vapor-grown carbon fiber is (1.5~2.5):1; (7) The second adhesive accounts for 5% to 10% of the total mass of the second active layer; (8) The second adhesive comprises polyvinylidene fluoride and polyacrylic acid, wherein the mass ratio of polyvinylidene fluoride and polyacrylic acid is 1:1.
[0038] Optionally, the silicon-based material includes at least one of micron-sized elemental silicon, micron-sized silicon-carbon material, or micron-sized silicon-oxygen material.
[0039] Optionally, the morphology of the silicon-based material is at least one of spherical, near-spherical, and blocky.
[0040] Optionally, the composite electrode sheet is a composite positive electrode sheet, wherein the first active layer comprises lithium iron phosphate, a third conductive agent and a third binder, and the second active layer comprises a high-nickel ternary material, a fourth binder and a fourth conductive agent; The third and fourth conductive agents are both selected from at least one of carbon nanotubes, conductive carbon black, or graphene. Both the third and fourth adhesives are selected from polyvinylidene fluoride or polyacrylic acid, and satisfy at least one of the following characteristics: (1) The mass ratio of the lithium iron phosphate, the third conductive agent and the third binder is (93~95):(3~4):(1.6~2.4); (2) The third conductive agent includes conductive carbon black and carbon nanotubes, and the mass ratio of the conductive carbon black to carbon nanotubes is (2~3.5):(0.5~2); (3) The mass ratio of the high-nickel ternary material, the fourth conductive agent, and the fourth binder is (94~97):(1.5~3):(1.6~2.4); (4) The fourth conductive agent includes conductive carbon black and graphene, wherein the mass ratio of conductive carbon black to graphene is (1~2.5):(0.5~1); (5) The mass ratio of the second active layer to the first active layer is (20~30): (70~80).
[0041] A second aspect of the present invention provides a method for preparing a composite electrode sheet, characterized by comprising at least the following steps: S1: Obtain the pretreated current collector; S2: Prepare a first slurry and a second slurry; coat the first slurry onto at least one side surface of the pretreated current collector along the thickness direction, dry it, and form a first active layer on at least one side surface of the current collector; etch the first active layer to obtain a first active layer including a first recess; S3: The second slurry is coated onto the first active layer including the first recess, dried, and a second active layer is formed on the surface of the first active layer away from the current collector. After rolling, the second active layer is etched to obtain a second active layer including the second recess, thus obtaining the composite electrode sheet.
[0042] Optionally, the composite electrode sheet is a composite negative electrode sheet, and satisfies at least one of the following characteristics: (1) The solid content of the first slurry is 48%~52%; (2) The viscosity of the first slurry is 2000 mPa·s to 3000 mPa·s; (3) The solid content of the second slurry is 42%~46%; (4) The viscosity of the second slurry is 800 mPa·s to 1500 mPa.
[0043] Further optionally, the solid content of the first slurry is 48% to 52%, which can be listed as 48%, 50%, 52%, or any value within the range of 48% to 52%.
[0044] Optionally, the viscosity of the first slurry is 2000 mPa·s to 3000 mPa·s, which can be listed as 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, or any value within the range of 2000 mPa·s to 3000 mPa·s. This invention controls the solid content of the first slurry to be 48% to 52%, and the viscosity to be 2000 mPa·s to 3000 mPa·s, to obtain a uniform, defect-free conductive underlayer, providing a good foundation for subsequent etching and secondary coating. A low solid content results in an excessively thin underlayer, affecting the mechanical interlocking depth reference; a high solid content or excessively high viscosity causes coating defects and deterioration of the etching morphology.
[0045] Optionally, the solid content of the second slurry is 42% to 46%, which can be listed as 42%, 44%, 46%, or any value within the range of 42% to 46%.
[0046] Optionally, the viscosity of the second slurry is 800 mPa·s to 1500 mPa·s, and can be listed as 800 mPa·s, 1000 mPa·s, 1100 mPa·s, 1500 mPa·s, or any value within the range of 800 mPa·s to 1500 mPa·s. This invention controls the solid content of the second slurry to be 42% to 46%, and the viscosity to be 800 mPa·s to 1500 mPa·s to ensure that the slurry fully fills the first recess, achieving a dense, void-free interface. Excessive solid content or viscosity will cause the top of the first recess to close prematurely and the bottom to be insufficiently filled.
[0047] Optionally, the composite electrode sheet is a composite positive electrode sheet, and satisfies at least one of the following characteristics: (1) The solid content of the first slurry is 53%~57%; (2) The viscosity of the first slurry is 3000 mPa·s to 4000 mPa·s; (3) The solid content of the second slurry is 50%~54%; (4) The viscosity of the second slurry is 1500 mPa·s to 2100 mPa·s.
[0048] Further optionally, the solid content of the first slurry is 53% to 57%, which can be listed as 53%, 55%, 57%, or any value within the range of 53% to 57%.
[0049] Optionally, the viscosity of the first slurry is 3000 mPa·s to 4000 mPa·s, which can be listed as 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, or any value within the range of 3000 mPa·s to 4000 mPa·s.
[0050] Optionally, the solid content of the second slurry is 50% to 54%, which can be listed as 50%, 52%, 54%, or any value within the range of 50% to 54%.
[0051] Optionally, the viscosity of the second slurry is 1500 mPa·s to 2100 mPa·s, which can be listed as 1500 mPa·s, 1800 mPa·s, 2000 mPa·s, 2100 mPa·s, or any value within the range of 1500 mPa·s to 2100 mPa·s.
[0052] Optionally, the preparation method satisfies at least one of the following characteristics: (1) The drying process in S2 uses a fast-then-slow airflow. (2) The drying process in S2 includes: drying at 60℃~70℃ with a wind speed of 0.5m / s~0.6m / s for 5~10 minutes, and then heating to 80℃~90℃ with a wind speed of 0.3m / s~0.4m / s for 20-30 minutes; (3) The drying process in S3 adopts a three-stage process of low temperature-medium temperature-high temperature; (4) The drying process in S3 includes: drying at 45℃~50℃ with a wind speed of 0.2m / s~0.3m / s for 8min~15min, then heating up to 75℃~80℃ with a wind speed of 0.3m / s~0.4m / s for 12-17min, and finally heating up to 100℃~120℃ with a wind speed of 0.2m / s~0.3m / s for 18~25min.
[0053] The first active layer of this invention employs a fast-then-slow drying process to ensure coating uniformity and the density of the conductive network. The second coating uses a three-stage slow drying process. The low-temperature, slow initial drying stage allows the slurry sufficient time to penetrate into the bottom of the microgrooves under capillary force, preventing premature surface drying at the top of the grooves and the formation of "bridging" seals that could lead to voids inside the grooves. The medium-temperature drying stage promotes uniform solvent evaporation and reduces internal stress in the coating. The high-temperature drying stage ensures that the binder is fully cured, enhancing interlayer bonding.
[0054] A third aspect of the present invention provides a battery comprising the composite electrode sheet as described above.
[0055] Beneficial effects: This invention provides a composite electrode sheet, its preparation method, and a battery, which have the following advantages: (1) The present invention creates a micro-interlocking structure at the interface by first etching the surface of the current collector, so that the first active layer and the second active layer are three-dimensionally combined, rather than the traditional two-dimensional planar adhesion. This effectively suppresses the shear stress generated by the active material when the volume changes during charging and discharging, fundamentally solves the coating peeling problem, and greatly improves the electrode cycle life.
[0056] (2) By controlling the depth of the first and second recesses and the area ratio of the deep recesses, the present invention solves the bottleneck of transmission imbalance in traditional electrodes. It is particularly beneficial for thick electrodes to achieve a balance between high energy density and high power density, and to achieve the optimal synergy between ion channel construction and mechanical interlock protection.
[0057] (3) By precisely controlling the solid content, viscosity and drying process of the slurry, the present invention ensures that the second slurry can fully fill the concave structure of the first active layer, avoids voids caused by insufficient filling in the concave, ensures the compactness of the interlocking between active layers, gives full play to the role of the micro-interlocking structure in enhancing the interlayer bonding force, and ensures the structural stability of the battery during cycling.
[0058] (4) The coating and etching technologies described in this invention are combinations and innovative applications of existing mature processes (such as blade coating, laser etching, and plasma treatment). They do not require expensive new equipment, are easy to upgrade and promote on existing production lines, and are applicable to various active material systems. Attached Figure Description
[0059] Figure 1 The first concave portion is distributed on the first surface.
[0060] Figure 2 The distribution pattern of the second recess on the second surface.
[0061] Figure 3 This is a structural diagram of the composite negative electrode sheet of Example 1, where 1 is the second active layer, 2 is the first active layer, and 3 is the copper foil current collector.
[0062] Figure 4 This is an exploded view of the composite negative electrode sheet of Example 1. From top to bottom, the image shows the second active layer, the first active layer, and the copper foil current collector. Detailed Implementation
[0063] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0064] Unless otherwise specified, all concentrations involved in this invention are mass concentrations, and all ratios are mass ratios; the room temperature is 25°C.
[0065] Example 1 This embodiment provides a composite negative electrode sheet and its preparation method, and a battery; the composite negative electrode sheet includes a copper foil current collector (thickness of 6μm) and a first active layer and a second active layer sequentially stacked on the copper foil current collector; The first active layer has a first surface away from the copper foil current collector, and a first recess is formed on the first active layer extending from the first surface toward the copper foil current collector; The second active layer covers the first surface and fills the first recess; the depth of the first recess is h1 = H1 × 30% = 5.4 μm, where H1 = 18 μm, which is the thickness of the first active layer; The width of the first recess is l1 = H1 × 100% = 18 μm; The first recesses are distributed in a dot matrix pattern on the first surface. (e.g.) Figure 1 (As shown) The second active layer has a second surface away from the first active layer, and a second recess is formed from the second surface toward the current collector, and the second recess includes a shallow recess and a deep recess. The depth of the deep recess is greater than the depth of the shallow recess, and the depth of the deep recess is greater than the thickness of the second active layer.
[0066] The depth h of the shallow recess 2.1 =H1×60%=10.8μm; the depth h of the deep recess 2.2 =c2×[c2 / (c1+c2)]×A×H=47.7μm, where c1=1.2g / cm 3 , where c2 is the compaction density of the first active layer; c2 = 1.6 g / cm³ 3 , where is the compaction density of the second active layer, H=55μm, is the total thickness of the composite negative electrode sheet, and A=0.95 is the system constant; The width l2 of the shallow recess and the width l3 of the deep recess are consistent, each being l1×100%=18μm independently.
[0067] The percentage of the projected area of the deep recess on the copper foil current collector plane to the total area of the copper foil current collector is c2 / (c1+c2)×ε=17%, where ε=30%, which is the total porosity of the composite negative electrode sheet.
[0068] The second recesses are distributed in a grid pattern on the second surface. (e.g.) Figure 2 (As shown) By weight percentage, the first active layer comprises 96% first conductive agent and 4% first binder.
[0069] By weight percentage, the second active layer comprises 89% silicon-carbon composite material, 7.5% second binder, and 3.5% second conductive agent; The first binder is polyvinylidene fluoride. The first conductive agent is artificial graphite, highly conductive carbon black, and graphene, wherein the mass ratio of the artificial graphite, conductive carbon black, and graphene is 85:12:1.5.
[0070] The silicon-carbon composite material is a silicon-based material and artificial graphite, and the mass ratio of the silicon-based material to the artificial graphite is 15:85.
[0071] The silicon-based material is a perfectly spherical, micron-sized elemental silicon.
[0072] The second adhesive is polyvinylidene fluoride and polyacrylic acid, wherein the mass ratio of polyvinylidene fluoride to polyacrylic acid is 1:1.
[0073] The second conductive agent is conductive carbon black and vapor-grown carbon fiber, and the mass ratio of conductive carbon black to vapor-grown carbon fiber is 2:1.
[0074] The method for preparing the composite negative electrode includes the following steps: S1: Obtaining the pretreated copper foil current collector: The copper foil current collector is cleaned by ultrasonic cleaning combined with ethanol wiping, and then subjected to plasma treatment at 100 W power for 2 min in an Ar / O2 mixed atmosphere (volume ratio 4:1) to obtain the pretreated copper foil current collector. S2: Prepare a first slurry and a second slurry; apply the first slurry to one side surface of the pretreated current collector along the thickness direction by a scraping method, dry it at 60°C with a wind speed of 0.5m / s for 5 minutes, then raise the temperature to 80°C and dry it at a wind speed of 0.3m / s for 25 minutes to form a first active layer on one side surface of the current collector; perform laser etching (wavelength 355nm) on the first active layer to obtain a first active layer including a first recess; S3: The second slurry is coated onto the first active layer including the first recess by a scraping method, and dried at 45°C with a wind speed of 0.2 m / s for 10 min. Then, the temperature is raised to 75°C and dried at a wind speed of 0.3 m / s for 15 min. Finally, the temperature is raised to 110°C and dried at a wind speed of 0.2 m / s for 20 min to form a second active layer on the surface of the first active layer away from the current collector. After rolling, the second active layer is laser etched (wavelength 355 nm) to obtain a second active layer including the second recess, thus obtaining the composite electrode sheet.
[0075] The first slurry has a solid content of 50% and a viscosity of 2500 mPa·s.
[0076] The second slurry has a solid content of 44% and a viscosity of 1100 mPa·s.
[0077] The battery includes the composite negative electrode sheet as described above.
[0078] Figure 3 This is a structural diagram of the composite negative electrode sheet in this embodiment. In the diagram, 1 is the second active layer, 2 is the first active layer, and 3 is the copper foil current collector.
[0079] Figure 4 This is an exploded view of the composite negative electrode sheet in this embodiment. From top to bottom, the layers are the second active layer, the first active layer, and the copper foil current collector.
[0080] Example 2 This embodiment provides a composite positive electrode sheet and its preparation method, and a battery; the composite positive electrode sheet has a thickness H=55μm and includes an aluminum foil current collector (thickness of 12μm) and a first active layer and a second active layer sequentially stacked on the aluminum foil current collector; The first active layer has a first surface away from the aluminum foil current collector, and a first recess is formed on the first active layer extending from the first surface toward the aluminum foil current collector. The second active layer covers the first surface and fills the first recess; the depth of the first recess is h1 = H1 × 30% = 7.5 μm, where H1 = 25 μm, which is the thickness of the first active layer; The width of the first recess is l1 = H1 × 100% = 25 μm; The first recess is distributed in a dot matrix pattern on the first surface.
[0081] The second active layer has a second surface away from the first active layer, and a second recess is formed from the second surface toward the current collector, and the second recess includes a shallow recess and a deep recess. The depth of the deep recess is greater than the depth of the shallow recess, and the depth of the deep recess is greater than the thickness of the second active layer.
[0082] The depth h of the shallow recess 2.1 =H1×60%=15μm; the depth h of the deep recess 2.2 =36μm.
[0083] The width l2 of the shallow recess and the width l3 of the deep recess are consistent, each being l1×100%=25μm independently.
[0084] The percentage of the projected area of the deep recess on the copper foil current collector plane to the total area of the copper foil current collector is c2 / (c1+c2)×ε=16%, where c1=2.4g / cm². 3 , where c2 is the compaction density of the first active layer; c2 = 3.2 g / cm³ 3 , where is the compaction density of the second active layer; ε = 28%, is the total porosity of the composite cathode sheet.
[0085] The second recess is distributed in a grid pattern on the second surface.
[0086] By weight percentage, the first active layer comprises 94.5% lithium iron phosphate, 3.5% third conductive agent and 2% third binder.
[0087] By weight percentage, the second active layer comprises 95.5% high-nickel ternary material, 2% fourth binder, and 2.5% fourth conductive agent; The third binder is polyvinylidene fluoride. The third conductive agent is highly conductive carbon black and carbon nanotubes, with a mass ratio of conductive carbon black to carbon nanotubes of 2.5:1.
[0088] The high-nickel ternary material is NCM811, sourced from Ningbo Ronbay New Energy Technology Co., Ltd.
[0089] The fourth adhesive is polyvinylidene fluoride.
[0090] The fourth conductive agent is conductive carbon black and graphene, and the mass ratio of conductive carbon black to graphene is 2:0.5.
[0091] The mass ratio of the second active layer to the first active layer is 25:75.
[0092] The method for preparing the composite positive electrode includes the following steps: S1: Obtaining the pretreated aluminum foil current collector: The copper foil current collector was cleaned by ultrasonic cleaning combined with ethanol wiping, and then subjected to plasma treatment at 100 W power for 2 min in an Ar / O2 mixed atmosphere (volume ratio 4:1) to obtain the pretreated copper foil current collector. S2: Prepare a first slurry and a second slurry; apply the first slurry to one side surface of the pretreated current collector along the thickness direction by a scraping method, dry it at 70°C with a wind speed of 0.5 m / s for 5 min, then raise the temperature to 90°C and dry it at a wind speed of 0.3 m / s for 25 min to form a first active layer on one side surface of the current collector; etch the first active layer to obtain a first active layer including a first recess; S3: The second slurry is coated onto the first active layer including the first recess by a scraping method, and dried at 50°C with a wind speed of 0.2 m / s for 10 min. Then, the temperature is raised to 80°C and dried at a wind speed of 0.3 m / s for 15 min. Finally, the temperature is raised to 110°C and dried at a wind speed of 0.2 m / s for 20 min to form a second active layer on the surface of the first active layer away from the current collector. After rolling, the second active layer is etched to obtain a second active layer including the second recess, thus obtaining the composite electrode sheet.
[0093] The first slurry has a solid content of 55% and a viscosity of 3500 mPa·s.
[0094] The second slurry has a solid content of 52% and a viscosity of 1800 mPa·s.
[0095] The battery includes the composite positive electrode sheet as described above.
[0096] Example 3 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Embodiment 1, except that the depth of the first recess is h1=H1×20%=3.6μm.
[0097] Example 4 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Embodiment 1, except that the depth of the first recess is h1=H1×40%=7.2μm.
[0098] Example 5 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 1, except that the depth h of the shallow concave portion is... 2.1 =H1×50%=9μm.
[0099] Example 6 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 1, except that the depth h of the shallow concave portion is... 2.1 =H1×70%=12.6μm.
[0100] Example 7 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 1, except that the depth h of the deep recess is... 2.2 =35μm.
[0101] Example 8 This embodiment provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 1, except that the depth h of the deep recess is... 2.2 =48μm.
[0102] Example 9 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in embodiment 2, except that the depth of the first recess is h1=H1×20%=5μm.
[0103] Example 10 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in embodiment 2, except that the depth of the first recess is h1=H1×40%=10μm.
[0104] Example 11 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 2, except that the depth h of the shallow concave portion is... 2.1 =H1×50%=12.5μm.
[0105] Example 12 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 2, except that the depth h of the shallow concave portion is... 2.1 =H1×70%=17.5μm.
[0106] Example 13 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 2, except that the depth h of the deep recess is... 2.2 =32μm.
[0107] Example 14 This embodiment provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Embodiment 2, except that the depth h of the deep recess is... 2.2 =38μm.
[0108] Comparative Example 1 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth of the first recess is h1=H1×12%=2.16μm.
[0109] Comparative Example 2 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth of the first recess is h1=H1×52%=9.36μm.
[0110] Comparative Example 3 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth h of the shallow concave portion is... 2.1 =H1×25%=4.5μm.
[0111] Comparative Example 4 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth h of the shallow concave portion is... 2.1 =H1×85%=15.3μm.
[0112] Comparative Example 5 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth h of the deep recess is different. 2.2 =28μm.
[0113] Comparative Example 6 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the depth h of the deep recess is different. 2.2 =54μm, and the projected area of the deep recess on the copper foil current collector plane accounts for 35% of the total area of the copper foil current collector.
[0114] Comparative Example 7 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the first slurry is 55% and the viscosity is 3800 mPa·s.
[0115] Comparative Example 8 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the first slurry is 50% and the viscosity is 1200 mPa·s.
[0116] Comparative Example 9 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the first slurry has a solid content of 50% and a viscosity of 4200 mPa·s. The second slurry has a solid content of 44% and a viscosity of 2000 mPa·s.
[0117] Comparative Example 10 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the second slurry is 38% and the viscosity is 600 mPa·s.
[0118] Comparative Example 11 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the second slurry is 52% and the viscosity is 2200 mPa·s.
[0119] Comparative Example 12 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the second slurry is 44% and the viscosity is 400 mPa·s.
[0120] Comparative Example 13 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the solid content of the second slurry is 44% and the viscosity is 2000 mPa·s.
[0121] Comparative Example 14 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that the drying process in S3 is as follows: drying at 75°C with a wind speed of 0.5 m / s for 10 min, followed by heating to 110°C and drying at a wind speed of 0.2 m / s for 30 min.
[0122] Comparative Example 15 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that the drying process in S3 is as follows: drying at 35°C with a wind speed of 0.1 m / s for 30 min, then heating to 75°C and drying at a wind speed of 0.3 m / s for 15 min, and finally heating to 100°C and drying at a wind speed of 0.2 m / s for 20 min.
[0123] Comparative Example 16 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the drying process in S3 is: drying at 110°C with a wind speed of 0.3 m / s for 45 min.
[0124] Comparative Example 17 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that the drying process in S3 is as follows: drying at 45°C with a wind speed of 0.5 m / s for 10 min, then heating to 75°C and drying at a wind speed of 0.6 m / s for 15 min, and finally heating to 100°C and drying at a wind speed of 0.5 m / s for 20 min.
[0125] Comparative Example 18 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the first conductive agent is artificial graphite, highly conductive carbon black, and graphene, and the mass ratio of the artificial graphite, conductive carbon black, and graphene is 90:8:0.5.
[0126] Comparative Example 19 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the first conductive agent is artificial graphite and highly conductive carbon black, and the mass ratio of the artificial graphite to the conductive carbon black is 86:12.
[0127] Comparative Example 20 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that the silicon-carbon composite material is a silicon-based material and artificial graphite, and the mass ratio of the silicon-based material to the artificial graphite is 5:95.
[0128] Comparative Example 21 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the silicon-carbon composite material is a silicon-based material and artificial graphite, and the mass ratio of the silicon-based material to the artificial graphite is 20:80.
[0129] Comparative Example 22 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that the silicon-carbon composite material is a silicon-based material and artificial graphite, and the mass ratio of the silicon-based material to the artificial graphite is 25:75.
[0130] Comparative Example 23 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the second conductive agent accounts for 2% of the total mass of the second active layer.
[0131] Comparative Example 24 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the second conductive agent accounts for 5% of the total mass of the second active layer.
[0132] Comparative Example 25 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the second conductive agent is conductive carbon black.
[0133] Comparative Example 26 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the second conductive agent is vapor-grown carbon fiber.
[0134] Comparative Example 27 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the mass ratio of the conductive carbon black to the vapor-grown carbon fiber is 1:1.
[0135] Comparative Example 28 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the mass ratio of the conductive carbon black to the vapor-grown carbon fiber is 3:1.
[0136] Comparative Example 29 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that, by weight percentage, the first active layer includes 97% of a first conductive agent and 3% of a first binder.
[0137] The silicon-carbon composite material is a silicon-based material and artificial graphite, and the mass ratio of the silicon-based material to the artificial graphite is 20:80.
[0138] Comparative Example 30 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that, by weight percentage, the first active layer includes 95% first conductive agent and 5% first binder.
[0139] The second conductive agent accounts for 2% of the total mass of the second active layer.
[0140] Comparative Example 31 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the depth of the first recess is h1=H1×12%=3μm.
[0141] Comparative Example 32 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the depth of the first recess is h1=H1×55%=13.8μm.
[0142] Comparative Example 33 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the depth h of the shallow concave portion is... 2.1 =H1×35%=8.8μm.
[0143] Comparative Example 34 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the depth h of the shallow concave portion is... 2.1 =H1×85%=21.3μm.
[0144] Comparative Example 35 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the depth h of the deep recess is... 2.2 =28μm.
[0145] Comparative Example 36 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the projected area of the deep recess on the copper foil current collector plane accounts for 8% of the total area of the copper foil current collector.
[0146] Comparative Example 37 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the projected area of the deep recess on the aluminum foil current collector plane accounts for 12% of the total area of the entire aluminum foil current collector.
[0147] Comparative Example 38 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the projected area of the deep recess on the aluminum foil current collector plane accounts for 20% of the total area of the entire aluminum foil current collector.
[0148] Comparative Example 39 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the projected area of the deep recess on the aluminum foil current collector plane accounts for 28% of the total area of the entire aluminum foil current collector.
[0149] Comparative Example 40 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the solid content of the second slurry is 48% and the viscosity is 1200 mPa·s.
[0150] Comparative Example 41 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the solid content of the second slurry is 58% and the viscosity is 2800 mPa·s.
[0151] Comparative Example 42 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 2, except that the solid content of the second slurry is 52% and the viscosity is 800 mPa·s.
[0152] Comparative Example 43 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the solid content of the second slurry is 52% and the viscosity is 2600 mPa·s.
[0153] Comparative Example 44 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the drying process in S3 is as follows: drying at 80°C with a wind speed of 0.6 m / s for 15 min, followed by heating to 110°C and drying at a wind speed of 0.4 m / s for 30 min.
[0154] Comparative Example 45 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the drying process in S3 is as follows: drying at 40°C with a wind speed of 0.2 m / s for 25 min, then heating to 80°C and drying at a wind speed of 0.4 m / s for 18 min, and finally heating to 110°C and drying at a wind speed of 0.3 m / s for 20 min.
[0155] Comparative Example 46 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the drying process in S3 is: drying at 110°C with a wind speed of 0.4 m / s for 50 min.
[0156] Comparative Example 47 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the drying process in S3 is as follows: drying at 50°C with a wind speed of 0.6 m / s for 12 min, then heating to 80°C and drying at a wind speed of 0.7 m / s for 18 min, and finally heating to 110°C and drying at a wind speed of 0.6 m / s for 20 min.
[0157] Comparative Example 48 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the solid content of the first slurry is 60% and the viscosity is 4200 mPa·s.
[0158] Comparative Example 49 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the solid content of the first slurry is 55% and the viscosity is 2200 mPa·s.
[0159] Comparative Example 50 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the solid content of the first slurry is 55% and the viscosity is 4800 mPa·s.
[0160] The second slurry has a solid content of 52% and a viscosity of 2600 mPa·s.
[0161] Comparative Example 51 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the first active layer includes 96% lithium iron phosphate, 2.5% third conductive agent and 1.5% third binder.
[0162] Comparative Example 52 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the first active layer includes 95% lithium iron phosphate, 3% third conductive agent and 2% third binder.
[0163] The third conductive agent is conductive carbon black.
[0164] Comparative Example 53 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the first active layer includes 95% lithium iron phosphate, 3.5% third conductive agent and 1.5% third binder.
[0165] The third conductive agent comprises conductive carbon black and carbon nanotubes, wherein the mass ratio of conductive carbon black to carbon nanotubes is 2.5:1.
[0166] Comparative Example 54 This comparative example provides a composite positive electrode sheet and its preparation method, and a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the second active layer includes 96% high-nickel ternary material, 3% fourth binder and 1% fourth conductive agent. The fourth conductive agent is conductive carbon black and graphene, and the mass ratio of conductive carbon black to graphene is 0.5:0.5.
[0167] Comparative Example 55 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the second active layer includes 96% high-nickel ternary material, 2% fourth binder and 2% fourth conductive agent. The fourth conductive agent is conductive carbon black.
[0168] Comparative Example 56 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the second active layer includes 96% high-nickel ternary material, 1.5% fourth binder, and 2.5% fourth conductive agent.
[0169] Comparative Example 57 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the mass ratio of the second active layer to the first active layer is 35:65.
[0170] Comparative Example 58 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the mass ratio of the second active layer to the first active layer is 45:55.
[0171] Comparative Example 59 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that the mass ratio of the second active layer to the first active layer is 15:85.
[0172] Comparative Example 60 This comparative example provides a composite positive electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 2, except that, by weight percentage, the first active layer includes 95% lithium iron phosphate, 2% third conductive agent and 3% third binder.
[0173] The third conductive agent comprises conductive carbon black and carbon nanotubes, wherein the mass ratio of conductive carbon black to carbon nanotubes is 1:1.
[0174] The mass ratio of the second active layer to the first active layer is 35:65.
[0175] Comparative Example 61 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as in Example 1, except that the mass ratio of the artificial graphite, conductive carbon black and graphene is 83:12:3.
[0176] Comparative Example 62 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that, by weight percentage, the first active layer includes 97% first conductive agent and 3% first binder.
[0177] Comparative Example 63 This comparative example provides a composite negative electrode sheet and its preparation method, as well as a battery. The specific implementation method is the same as that in Example 1, except that, by weight percentage, the first active layer includes 95% first conductive agent and 5% first binder.
[0178] Comparative Example 64 This comparative example uses a composite negative electrode and battery prepared by traditional single-layer coating. The preparation method includes the following steps: S1: Obtaining the pretreated copper foil current collector: The copper foil current collector is cleaned by ultrasonic cleaning combined with ethanol wiping, and then subjected to plasma treatment at 100W power for 2 minutes in an Ar / O2 mixed atmosphere (volume ratio 4:1) to obtain the pretreated copper foil current collector. S2: Prepare the negative electrode slurry; weigh each raw material according to the formula in the table below, add solvent and mix evenly to obtain a single-layer negative electrode slurry; the slurry solid content is 46% and the viscosity is 1800 mPa·s. Apply the negative electrode material to one side of the pretreated current collector along the thickness direction using a scraping method, dry at 70°C with a wind speed of 0.5 m / s for 5 min, then raise the temperature to 90°C and dry at a wind speed of 0.3 m / s for 25 min to form an active layer on one side of the current collector. Roll press to obtain the negative electrode sheet.
[0179] The negative electrode comprises a 6μm thick copper foil current collector and a single-layer active coating on one side of the current collector; the total coating thickness after compaction is 49μm, and the total electrode thickness is 55μm, consistent with the total thickness of the composite negative electrode in Example 1; the coating compaction density is 1.45g / cm³. 3 The total areal density matches that of the two layers in Example 1. The formulation of the negative electrode active layer is shown in Table 1 below: Table 1
[0180] Comparative Example 65 This comparative example uses a composite cathode sheet and battery prepared by traditional single-layer coating. The preparation method includes the following steps: S1: Obtaining the pretreated aluminum foil current collector: The aluminum foil current collector is cleaned by ultrasonic cleaning combined with ethanol wiping, and then subjected to plasma treatment at 100 W power for 2 min in an Ar / O2 mixed atmosphere (volume ratio 4:1) to obtain the pretreated copper foil current collector. S2: Prepare the positive electrode slurry; weigh each raw material according to the formula in the table below, add N-methylpyrrolidone (NMP) solvent and mix and stir evenly to obtain a single-layer positive electrode slurry; the slurry solid content is 54% and the viscosity is 2800 mPa·s; coat the positive electrode material onto one side of the pretreated current collector along the thickness direction by scraping, dry at 50°C with a wind speed of 0.2 m / s for 10 min, then heat to 80°C and dry at a wind speed of 0.3 m / s for 15 min, and finally heat to 110°C and dry at a wind speed of 0.2 m / s for 20 min to form an active layer on the surface of the first active layer away from the current collector, and obtain the positive electrode sheet after rolling.
[0181] The positive electrode comprises a 12μm thick aluminum foil current collector and a single-layer active coating on one side of the current collector; after roll pressing, the total coating thickness is 43μm, and the total electrode thickness is 5μm, consistent with the total thickness of the composite positive electrode in Example 2; the total areal density of the coating matches the total areal density of the two layers in Example 2, and the overall compaction density is approximately 2.6 g / cm³. 3 .
[0182] The positive electrode active layer formulation is shown in Table 2 below: Table 2
[0183] Performance testing The samples prepared in the examples and comparative examples were subjected to the following performance tests. The test items and test results for each example are shown in Tables 3 to 10. In the tables, " / " indicates that the test item was not performed.
[0184] 1. Peeling Force: Cut the electrode sheet into strips of standard width (e.g., 25mm), and use double-sided tape to smoothly attach the coated side to a clean steel plate. Clamp one end of the electrode sheet with a tensile testing machine and peel it off at a constant speed (e.g., 50mm / min) at a 90° angle. Record the average force value throughout the peeling process, usually expressed in N / m.
[0185] 2. Capacity retention rate after 100 cycles at 1C: Charge the battery with a constant current of 1C until the charging cutoff voltage is reached, then charge with a constant voltage until the current is less than or equal to 0.05C, at which point charging ends; discharge with a constant current of 1C until the discharge cutoff voltage is reached, and record the capacity C0; repeat the above steps 100 times, and record the capacity of the 100th cycle as C. 100 Capacity retention rate = C 100 / C0*100% 3. EIS test: The load is adjusted to 50%, and the test is carried out with a 5mV voltage disturbance from 0.01Hz to 1000000Hz.
[0186] 4. Rate Performance: The composite positive electrode is charged at a constant current of 0.5C to the charging cutoff voltage, and then charged at a constant voltage until the current is less than or equal to 0.05C, at which point charging ends. It is then discharged at a constant current of 0.5C to the discharge cutoff voltage, and the capacity C is recorded. 0.5; Charge the battery with a constant current of 3.0C until the charging cutoff voltage is reached, then charge with a constant voltage at the cutoff voltage until the current is less than or equal to 0.05C, at which point charging is complete. Discharge the battery with a constant current of 3.0C until the discharge cutoff voltage is reached, and record the capacity C. 3.0 The rate capability is C. 3.0 / C 0.5 .
[0187] The composite negative electrode is charged with a constant current of 0.2C until the charging cutoff voltage is reached, and then charged with a constant voltage at the cutoff voltage until the current is less than or equal to 0.05C, at which point charging ends. The battery is then discharged with a constant current of 0.2C until the discharge cutoff voltage is reached, and the capacity C is recorded. 0.2 Charge the battery with a constant current of 2.0C until the charging cutoff voltage is reached, then charge with a constant voltage at the cutoff voltage until the current is less than or equal to 0.05C, at which point charging is complete. Discharge the battery with a constant current of 2.0C until the discharge cutoff voltage is reached, and record the capacity C. 2.0 The rate capability is C. 2.0 / C 0.2 .
[0188] 5. Volume resistivity: The sample is placed on a test stage with four equally spaced probes. A constant pressure is applied to the coating, a constant current is passed through the two outer probes, and the voltage drop is measured on the two inner probes. The resistivity is calculated using a formula. The unit is usually Ω·cm, and the lower the value, the better the conductivity of the coating.
[0189] 6. Compacted density: Compacted density (g / cm³) 3 = Surface density / Coating thickness; Surface density: Cut a piece of electrode with a known area (A), weigh it, and subtract the mass of the blank current collector to obtain the coating mass (m). Surface density = m / A. Coating thickness: Measure the total thickness of the electrode using a micrometer or thickness gauge, and subtract the current collector thickness to obtain the coating thickness (d).
[0190] 7. Initial Coulomb Efficiency: Initial Discharge Capacity / Initial Charge Capacity.
[0191] 8. Volume expansion rate: Volume expansion rate (%) = (Thickness of fully charged / fully discharged electrode - Initial electrode thickness) / Initial electrode thickness × 100%.
[0192] 9. Energy density: Mass energy density (Wh / kg): Under standard conditions, the energy of the battery is recorded as discharge energy (discharge capacity × average discharge voltage) and then divided by the total mass of the battery.
[0193] Table 2
[0194] Table 2 shows that traditional single-layer coating (Comparative Example 64) has no etched structure, and the interlayer bonding relies solely on the physical adhesion between the coating and the current collector. Without mechanical interlocking or ion channel optimization, it exhibits the lowest peel strength, the most severe cycle decay, and the largest increase in interfacial impedance. In Comparative Examples 1 and 2, and Comparative Examples 31 and 32, both excessively shallow or deep first recesses lead to decreased interlayer bonding, making the active layer prone to delamination during cycling, accelerating the increase in interfacial impedance, and reducing capacity retention.
[0195] Table 3
[0196] Table 3 shows that when the depth h of the shallow concave portion... 2.1 2.1 When the etching depth exceeds 70%, excessive etching damages the structural integrity of the first active layer and harms the conductive network. When the depth h of the deep recess... 2.2 When the depth is too shallow (Comparative Example 5, Comparative Example 35), the deep recess does not reach the first active layer, limiting rate performance; when h 2,2 When the second recess is too deep and the proportion of the deep recess is too high (Comparative Example 6), the second recess penetrates into the aluminum foil current collector, causing the current collector to be exposed, the electronic path to be damaged, and the risk of micro short circuit.
[0197] The data above indicates that the depths of the first and second recesses, as well as the proportion of the deep recess, must be controlled within a defined range to achieve optimal synergy between "ion channel construction" and "mechanical interlocking protection." Deviation of any parameter will lead to performance degradation.
[0198] Table 4
[0199] Table 4 shows that controlling the viscosity, solid content, and drying process of the second slurry ensures that the slurry fully fills the grooves of the first recess, achieving a dense, void-free interface. Excessive solid content or viscosity leads to premature closure of the groove top and insufficient filling of the bottom; excessively rapid initial drying or high air velocity during the drying process also causes a "bridging" defect at the top of the groove, severely weakening the interfacial bonding force. The samples prepared in Examples 1 and 2 exhibited the highest peel strength of 24.5 N / m, a capacity retention rate of ≥90% after 100 cycles at 1C, and an interfacial impedance increase of only 1.02 times / 1.05 times, demonstrating optimal overall performance and verifying the rationality and necessity of the differentiated coating process parameter design in this application.
[0200] Table 5
[0201] Table 5 shows that in the negative electrode system, the addition of graphene significantly reduces the volume resistivity of the active layer, but excessive addition leads to a decrease in compaction density. When the binder content is below 3%, the peel force with the current collector decreases by more than 30%. In the positive electrode system, the addition of carbon nanotubes significantly reduces the volume resistivity. When the binder content is below 1.5%, the peel force with the aluminum foil current collector decreases by more than 32%. Optimal balance between conductivity and compaction density can be achieved by controlling the total amount of the third conductive agent at 3-4%.
[0202] Table 6
[0203] Table 6 shows that both too low and too high a proportion of silicon-based materials in silicon-carbon composites can lead to a decrease in cycle retention. Example 1 achieves the best balance between capacity, cycle stability and volume expansion.
[0204] Table 7
[0205] Table 7 shows that the selection and dosage of raw materials in conductive agents both affect the performance of the product.
[0206] Table 8
[0207] Table 8 shows that in composite cathode sheets, the mass ratio of the second active layer to the first active layer is preferably 25:75. When the proportion of the second active layer is too low, the energy density is insufficient (175Wh / kg). When the proportion of the second active layer is too high, the cycle stability decreases (78%). When the proportion of the second active layer is too high, the cycle retention rate drops to 65%, and the volume effect leads to an increase in interfacial stress.
[0208] Table 9
[0209] Table 9 shows that, by controlling the selection and amount of each raw material in the first and second active layers, Examples 1 and 2 synergistically improve the energy density, power density, cycle stability, and safety of lithium-ion batteries, achieving an excellent overall performance rating. This fully verifies that the raw material ratio design proposed in this application can effectively improve the overall performance of the composite electrode sheet and meet the requirements of high-energy-density power batteries.
[0210] The above provides a detailed description of a composite electrode sheet, its preparation method, and the battery provided by the present invention. It should be noted that the above description of the embodiments is only for the purpose of helping to understand the method and core idea of the present invention. The series of detailed descriptions listed in the present invention are only specific descriptions of feasible implementation methods of the present technology. They are not intended to limit the scope of protection of this application. All equivalent implementation methods or modifications made without departing from the spirit of the present application should be included within the scope of protection of this application.
Claims
1. A composite electrode sheet, characterized in that, The composite electrode sheet includes a current collector and a first active layer and a second active layer sequentially stacked on the current collector; The first active layer has a first surface away from the current collector, and a first recess is formed on the first active layer extending from the first surface toward the current collector. The second active layer covers the first surface and fills the first recess; The second active layer has a second surface away from the first active layer, and a second recess is formed from the second surface toward the current collector, and the second recess includes a shallow recess and a deep recess. The depth of the deep recess is greater than the depth of the shallow recess, and the depth of the deep recess is greater than the thickness of the second active layer.
2. The composite electrode sheet according to claim 1, characterized in that, The composite electrode sheet satisfies at least one of the following characteristics: (1) The depth of the first recess is h1 = H1 × (20%~40%), where H1 is the thickness of the first active layer; (2) The width l1 of the first recess is H1×(80%~120%), where H1 is the thickness of the first active layer; (3) The depth h1 of the first recess is 3.6 μm to 10 μm; (4) The width l1 of the first recess is 14.4 μm to 30 μm; (5) The thickness H1 of the first active layer is 17 μm to 26 μm; (6) The compaction density c1 of the first active layer is 1.2 g / cm³. 3 ~2.4g / cm 3 .
3. The composite electrode sheet according to claim 1, characterized in that, The composite electrode sheet satisfies at least one of the following characteristics: (1) The depth h of the shallow concave portion 2.1 =H1×(50%~70%), where H1 is the thickness of the first active layer; (2) The depth h of the deep recess 2.2 =c2×[c2 / (c1+c2)]×A×H, where c1 and c2 are the compaction densities of the first and second active layers, respectively, H is the total thickness of the composite electrode sheet, and A is the system constant; (3) The width l2 of the shallow recess and the width l3 of the deep recess are consistent, and each is independently l1×(80%~120%); (4) The depth h of the shallow concave portion 2.1 Its thickness ranges from 9μm to 17.5μm; (5) The depth h of the deep recess 2.2 The thickness ranges from 32μm to 48μm. (6) The width l2 of the shallow recess and the width l3 of the deep recess are each independently 14.4 μm to 30 μm; (7) The compaction density c2 of the second active layer is 1.6 g / cm³. 3 ~3.2g / cm 3 ; (8) The ratio of the area of the deep recess to the total area of the composite electrode sheet is c2 / (c1+c2)×ε, where c1 and c2 are the compaction densities of the first active layer and the second active layer, respectively, and ε is the total porosity of the composite electrode sheet. (9) The area of the deep recess accounts for 14% to 18% of the total area of the composite electrode sheet.
4. The composite electrode sheet according to any one of claims 1 to 3, characterized in that, The composite electrode sheet satisfies at least one of the following characteristics: (1) The distribution pattern of the first recess on the first surface is grid-like, dot-matrix-like, or wavy; (2) The distribution pattern of the second recess on the second surface is grid-like, herringbone, straight, or diagonal; (3) The total thickness H of the composite electrode sheet is 54μm~66μm; (4) The total porosity ε of the composite electrode sheet is 28%~30%.
5. The composite electrode sheet according to any one of claims 1 to 3, characterized in that, N active layers are sequentially stacked on the second surface of the second active layer, and the N active layers have an Nth recess.
6. A method for preparing a composite electrode sheet according to any one of claims 1 to 5, characterized in that, At least the following steps are included: S1: Obtain the pretreated current collector; S2: Prepare a first slurry and a second slurry; coat the first slurry onto at least one side surface of the pretreated current collector along the thickness direction, dry it, and form a first active layer on at least one side surface of the current collector; etch the first active layer to obtain a first active layer including a first recess; S3: The second slurry is coated onto the first active layer including the first recess, dried, and a second active layer is formed on the surface of the first active layer away from the current collector. After rolling, the second active layer is etched to obtain a second active layer including the second recess, thus obtaining the composite electrode sheet.
7. The preparation method according to claim 6, characterized in that, The composite electrode sheet is a composite negative electrode sheet and satisfies at least one of the following characteristics: (1) The solid content of the first slurry is 48%~52%; (2) The viscosity of the first slurry is 2000 mPa·s to 3000 mPa·s; (3) The solid content of the second slurry is 42%~46%; (4) The viscosity of the second slurry is 800 mPa·s to 1500 mPa·s.
8. The preparation method according to claim 6, characterized in that, The composite electrode sheet is a composite positive electrode sheet and satisfies at least one of the following characteristics: (1) The solid content of the first slurry is 53%~57%; (2) The viscosity of the first slurry is 3000 mPa·s to 4000 mPa·s; (3) The solid content of the second slurry is 50%~54%; (4) The viscosity of the second slurry is 1500 mPa·s to 2100 mPa·s.
9. The preparation method according to claim 6, characterized in that, The preparation method satisfies at least one of the following characteristics: (1) The drying process in S2 uses a fast-then-slow airflow. (2) The drying process in S2 includes: drying at 60℃~70℃ with a wind speed of 0.5m / s~0.6m / s for 5~10 minutes, and then heating to 80℃~90℃ with a wind speed of 0.3m / s~0.4m / s for 20-30 minutes; (3) The drying process in S3 adopts a three-stage process of low temperature-medium temperature-high temperature; (4) The drying process in S3 includes: drying at 45℃~50℃ with a wind speed of 0.2m / s~0.3m / s for 8min~15min, then heating up to 75℃~80℃ with a wind speed of 0.3m / s~0.4m / s for 12-17min, and finally heating up to 100℃~120℃ with a wind speed of 0.2m / s~0.3m / s for 18~25min.
10. A battery, characterized in that, It includes the composite electrode sheet described in any one of claims 1 to 5, or the composite electrode sheet prepared by the preparation method according to any one of claims 6 to 9.